Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1881)
Demorest's Family Magazine. December 1881. Vol. 18, No. 2. -- Kith and Kin -- Algerian Sketches -- Something about New Year's Cards -- A German Christmas -- The Philosophy of Giving -- Christmas Gifts -- Spare the Woods -- Christmas Waits -- Fight of an Ermine and a Rat -- The Pest Dog -- The Lost Atlantis -- Give Me a Penny! -- Sir Joshua Reynolds -- Talks with Women -- Among the Pets -- Bunchie's Christmas -- Ophelia -- What Women are Doing -- What Women are Doing -- Current Topics -- Kitchen -- A Hint to Young Girls -- Scientific -- Diamonds of Thought -- Spice Box -- Mirror of Fashions -- Ladies' Club -- Review of New Publications -- The Lion's Bride --
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print, Valdosta State University Archives and Special Collections, October 24, 2016.
Keywords: Demorest's Family Magazine; Magazine; Illustrated Periodicals; Periodicals; Travel; Dressmaking; Homemaking; Needlework; Women; Catalogue; Children; Social History; Women's History; Fashion; United States; 1800s; 19th Century